2022
DOI: 10.1186/s13014-022-02144-w
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated proton therapy for early-stage glottic cancer: high-precision approach to laryngeal function preservation with exceptional treatment tolerability

Abstract: Background Due to the increasing expertise in transoral laser surgery and image-guided radiation therapy, treatment outcomes have recently improved in patients with early-stage glottic cancer. The objective of the current study was to evaluate intensity-modulated proton therapy (IMPT) as novel treatment option. Methods A total of 15 patients with T1-2N0 glottic squamous cell carcinoma, treated between 2017 and 2020, were evaluated. Toxicity was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several dosimetric studies have shown that IMPT can reduce dose delivery to risk organs in the treatment of various sites (23)(24)(25)(26). Moreover, several clinical outcomes of IMPT, including head and neck cancer, thoracic esophageal cancer, and BSTs, have demonstrated that favorable dose distribution using IMPT reduced adverse events (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Several dosimetric studies have shown that IMPT can reduce dose delivery to risk organs in the treatment of various sites (23)(24)(25)(26). Moreover, several clinical outcomes of IMPT, including head and neck cancer, thoracic esophageal cancer, and BSTs, have demonstrated that favorable dose distribution using IMPT reduced adverse events (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%